2021
DOI: 10.1080/13696998.2021.1965389
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilization and expenditures associated with hyperkalemia management: a retrospective study of Medicare Advantage patients

Abstract: Declaration of fundingThis study was funded by Vifor Pharma, Inc. Authors employed by Vifor Pharma, Inc., (PJA and SDW) were involved in the study design, data acquisition, results interpretation, and contributed to the intellectual content during manuscript drafting and revisions. Declaration of financial/other interestsNRD works under contract with the Centers for Medicare and Medicaid Services to develop and maintain performance measures used for public reporting and pay for performance programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…A similar reduction in all-cause medical costs with long-term anti-hyperkalemia therapy was also reported in an earlier, US-based, real-world insurance claims database study of long-term treatment with patiromer. 19 In this matched cohort study, 6 months of continuous patiromer exposure was associated with a significant 19% reduction in all-cause medical costs ($5212.00 per patient) compared with no oral anti-hyperkalemia therapy ( P <0.05). 19 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…A similar reduction in all-cause medical costs with long-term anti-hyperkalemia therapy was also reported in an earlier, US-based, real-world insurance claims database study of long-term treatment with patiromer. 19 In this matched cohort study, 6 months of continuous patiromer exposure was associated with a significant 19% reduction in all-cause medical costs ($5212.00 per patient) compared with no oral anti-hyperkalemia therapy ( P <0.05). 19 …”
Section: Discussionmentioning
confidence: 78%
“…A retrospective study demonstrated a 19% reduction in the rate of spending for all-cause medical costs among patients on patiromer therapy compared with those who did not receive any oral anti-hyperkalemia therapy, with a cost reduction of 34% in patients with inpatient or emergency department (ED) visits. 19 These reductions offset the increase in all-cause outpatient pharmacy costs in this study. 19 In the non-comparative, real-world RECOGNIZE I study in patients with hyperkalemia who received SZC treatment in the outpatient setting, the proportions of patients with hyperkalemia-related and all-cause inpatient hospitalizations were significantly reduced among patients who received long-term (>90 days) versus short-term (≤90 days) SZC therapy.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…While the cost of the novel potassium binders has been invoked to limit their use, a recent propensity matched study of patients with a K + >5.0 mmol/L either receiving or not receiving patiromer found that the use of patiromer was associated with a reduction in both hospitalizations and emergency room encounters associated with a significant reduction in costs. 12…”
Section: The Use Of a Non-steroidal Mramentioning
confidence: 99%
“…While fewer episodes of HK are likely with the non‐steroidal than the steroidal MRAs, when HK is encountered or anticipated, such as in patients with an estimated glomerular filtration rate <45 ml/min/1.73 m 2 , the new potassium binders such as patiromer or sodium zirconium cyclosilicate, both of which have enabled sustained normokalaemia for at least a year in patients on an MRA, 11 can be administered. While the cost of the novel potassium binders has been invoked to limit their use, a recent propensity matched study of patients with a K + >5.0 mmol/L either receiving or not receiving patiromer found that the use of patiromer was associated with a reduction in both hospitalizations and emergency room encounters associated with a significant reduction in costs 12 …”
Section: Constructive Proposals To Increase the Use Of Mineralocortic...mentioning
confidence: 99%